Early CT and MRI signs of invasive fungal sinusitis complicating COVID-19 infection: case report - Ahmed Samir; Mohamed Said Abdel-Gawad; Amr Magdy Elabd; Walid Mohamed Abed; Ayman Mahmoud; Tamer Yousry Gaweesh; Ahmed Youssef (The Egyptian Journal of Otolaryngology, 2022)
Abstract Background Corticosteroids are usually prescribed for severe cases with SARS-CoV-2 (COVID-19). Despite their importance to decrease patients’ mortality, they can cause serious side effects like fulminant fungal infection that can damage lungs or invade the sinuses then rapidly spread to the orbit and even intra-cranially. Unless early diagnosed and properly managed, patients can lose their vision or die from cavernous sinus thrombosis or other intracranial complications. Case presentation A 71-year-old diabetic male patient presented with dry cough, fever, and dyspnea for 6 days. PCR test for COVID-19 was ordered and declared positive. The oxygen saturation on day 7 started to decline to reach 90%. Eight ampules of intra-muscular dexamethasone were prescribed. The patient’s dyspnea improved, and the oxygen saturation reached 94% by day 13. Oral prednisone was prescribed in a withdrawal protocol. Unfortunately, on day 15, the patient complained of mild left-sided cheek swelling and noticeably dropped left angle of mouth. Neurological consultation suspected facial palsy and asked for brain MRI examination. Limited lower cuts of the MRI study that covered the left maxillary antrum revealed mild fullness of the pre-maxillary fat planes with mucosal thickening. Complimentary dedicated MRI and CT cuts over the left maxillary sinus showed localized signs of invasive fungal sinusitis without orbital or intracranial complications. The patient received antifungal therapy even before evident endoscopic findings appeared. He underwent endoscopic debridement few days after and he had an excellent outcome without any progression or significant morbidities. Conclusion Early CT/MRI radiological signs of invasive fungal sinusitis that complicated COVID-19 infection aid in the diagnosis and proper timely management of this fatal disease.